(untitled) (Journal of Mathematical Study, 2025)
In this paper we are interested in the existence of solutions for Dirichlet problem associated to the degenerate nonlinear elliptic equations in the setting of the weighted Sobolev spaces W^1,p_ 0 (Ω,ω).